Inferior Repositioning of Coronoid Process for the Treatment of Temporomandibular Joint Subluxation/Dislocation - Krishnakumar Raja, V. B. (Ann Maxillofac Surg, 2019)
Subluxation/dislocation of the temporomandibular joint (TMJ) is characterized by transient locking of the jaw following wide mouth opening. The etiology of the condition is multifactorial relating to hard-tissue or soft-tissue components of the joint. Myriad treatment procedures have been described in the literature, each with its own advantages and disadvantages. We present a new intraoral technique of coronoid repositioning for the treatment of TMJ subluxation/dislocation.